1978
DOI: 10.1063/1.324978
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and electronic structure of UO2

Abstract: The near normal incidence reflectivity of UO2 single crystals has been measured in the photon energy range from 0.03 eV to 13 eV. From the reflectivity spectrum the complex dielectric function ε (ω) =ε1(ω)+iε2(ω) has been derived by means of the Kramers-Kronig relation. In addition the absorption coefficient was determined from a direct transmission measurement on thin single crystal plates in the weakly absorbing spectral region below the absorption edge. An energy level scheme is proposed which allows a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
93
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 6 publications
24
93
3
1
Order By: Relevance
“…Following the work by Dudarev et al, Yun et al [18,19] performed a DFT+U calculation (U = 4.50 eV and J = 0.50 eV) on the antiferromagnetic ground state of UO 2 . Similar DFT+U calculations (U = 4.772eV and J = 0.511 eV) by Yu et al [20] obtained a band gap of 2.1 eV, which is consistent with the experimental value [2]. All these calculations indicated that the DFT+U method has been successfully applied to study the properties of uranium dioxide.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Following the work by Dudarev et al, Yun et al [18,19] performed a DFT+U calculation (U = 4.50 eV and J = 0.50 eV) on the antiferromagnetic ground state of UO 2 . Similar DFT+U calculations (U = 4.772eV and J = 0.511 eV) by Yu et al [20] obtained a band gap of 2.1 eV, which is consistent with the experimental value [2]. All these calculations indicated that the DFT+U method has been successfully applied to study the properties of uranium dioxide.…”
Section: Introductionsupporting
confidence: 63%
“…Owing to its technological relevance in the nuclear power industry and its significance from fundamental scientific point of view, uranium dioxide is intensely studied both experimentally [1][2][3][4][5] and theoretically [6][7][8]. One of the challenging research topics about uranium dioxide is the reactions of uranium dioxide with water, which it is associated with many fundamental phenomena related to hydrogen production [9,10], corrosion [11] and modifications of crystal morphologies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[27] The band maximum at 218 nm corresponds to the 5f 2 Ǟ 6dt 2g 5f 1 transition, while the lower energy band can be assigned to the 5f 2 Ǟ 6de g 5f 1 transition with a shoulder from spin orbit splitting. [28] However, DEG also exhibits an absorption band with a maximum at ca. 325 nm.…”
Section: (Jcpds [36-0089])mentioning
confidence: 99%
“…8 eV). [28] Whereas the oxygen K-edge XAS measurements suggest a f-f type band transition, the optical spectra propose that UO 2 is a f-d type since upon excitation neither the O 2p nor the U 5f electrons can access the unoccupied 5f state but only the unoccupied 6d state according to dipole selection rules. [29] The bandgap of the material was determined using the Tauc formula for direct bandgap materials.…”
Section: (Jcpds [36-0089])mentioning
confidence: 99%
“…Consequently, the sputtering of thin-film coatings of laser elements based on metallic uranium can strongly affect laser media which use photodissociation under the action of the radiation from inert-gas excimers for pumping. The optical properties of uranium dioxide UO 2 have been studied in [13]. Uranium dioxide is transparent in the range ˙ω < 2 eV.…”
mentioning
confidence: 99%